Estudio jurídico y doctrinario del capítulo primero de la ley del anciano y del art. 36 de la Constitución de la república del Ecuador. Propuesta de reforma - Avendaño González, Alba Sara (2016)
According to the Dictionary of the Spanish Language of the twentieth edition, he/she gives us a description of what Ancianidad means that is the man or the woman that he/she has many years and of what is characteristic of such people, and starting from this description he/she is born that that now call Centers Geriatrics, to be able to help these women of the third age or mature bigger as it Specifies it the Old man's Law, but it is necessary to stand out that some Public Entities don't give him the value that these women have, since they are human beings that gave their life as much as mother in their youth moment, or I eat Public or Private servants, reason for which I govern myself to give my point of view like Law student and to obtain a favorable result, since I see that even in the society this discrimination type is given toward these women, and that it should be sanctioned this crime with the most rigorous laws for these people that don't have feelings, they can already be its mothers, to its grannies, or to its own wives, since we see all so much aggression type that being of domestic, psychological type can, and studying the Law of the Old man from the Ecuador, I realized that the Rights of the women of the third age or mature adults are harmed in an or another way, since the main objective of this topic of Thesis is to eradicate the discrimination, the abandonment, and the forgetfulness completely toward these mothers of families, and that they are abandoned and abandoned and that its only company is the solitude. I motivate for which a not wanted Death is given, and that he/she would give me a lot of pain and sadness, to know that the State and the family doesn't worry about the health, feeding, and these ladies' company that you/they truly need since it they become harmed beings and victims of the wickedness of the men, and us as youths we should make protection campaigns and non abuses to the Ancianidad, and to be able to give good results to the society and power to reinstate them to its family so that they feel accompanied and they can have this way a worthy age and full with happiness next to its relatives, and that the death arrives him when God decides it, not in the complete abandonmen